2002
DOI: 10.1016/s0002-9440(10)61124-8
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Callus Size and Cartilage Synthesis in α1β1 Integrin-Deficient Mice during Bone Fracture Healing

Abstract: Integrins mediate cell adhesion to extracellular matrix components. Integrin alpha 1 beta 1 is a collagen receptor expressed on many mesenchymal cells, but mice deficient in alpha 1 integrin (alpha1-KO) have no gross structural defects. Here, the regeneration of a fractured long bone was studied in alpha1-KO mice. These mice developed significantly less callus tissue than the wild-type (WT) mice, and safranin staining revealed a defect in cartilage formation. The mRNA levels of nine extracellular matrix genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 41 publications
4
59
1
3
Order By: Relevance
“…As mentioned above, integrin α1β1 is expressed in chondrocytes and osteogenic cells. Reduced callus size and reduced cartilage production have been observed in bone fracture healing experiments, and it has been suggested that these effects correlate with a proliferation defect within mesenchymal precursor cells that occurs in the absence of α1β1 (Ekholm et al, 2002). Independent experiments have later demonstrated that osteoarthritis is accelerated in the absence of α1 (Zemmyo et al, 2003).…”
Section: α10β1mentioning
confidence: 99%
“…As mentioned above, integrin α1β1 is expressed in chondrocytes and osteogenic cells. Reduced callus size and reduced cartilage production have been observed in bone fracture healing experiments, and it has been suggested that these effects correlate with a proliferation defect within mesenchymal precursor cells that occurs in the absence of α1β1 (Ekholm et al, 2002). Independent experiments have later demonstrated that osteoarthritis is accelerated in the absence of α1 (Zemmyo et al, 2003).…”
Section: α10β1mentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] Open techniques have been used to create murine femoral fractures secured both by external [33][34][35] and internal fixation. 36 Despite the small size, the healing of fractures of the murine tibia stabilized using an external fixator has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…An inflammatory reaction exerts a substantial effect on adult skeletal repair (Simon et al, 2002), whereas the immune system has no known role in fetal skeletogenesis. Likewise, skeletal progenitor cells abound in the fetus, whereas they may be limited in number in the adult (Bruder et al, 1994;Ekholm et al, 2002).…”
Section: Introductionmentioning
confidence: 99%